PERTANGGUNGJAWABAN HARTA PRIBADI PEMEGANG SAHAM PERSEROAN TERBATAS DI INDONESIA - Gideon Paskha Wardhana (Arena Hukum, 2019)
AbstractThis research is intended to understand the purpose of the adoption of the doctrine of piercing the corporate veil (